Preliminary seismic analysis and strengthening proposals of two churches in Azores - Aníbal Costa (2005)
This paper covers the seismic behaviour modelling and numeric analysis of two church structures on Pico Island, Azores, affected by the Faial earthquake on 9 July 1998. The observed damages are first described and some modelling options for the analysis are discussed, particularly in what concerns the way of including the roof as a means of bracing the bearing walls. Frequencies and vibration modes are analysed and discussed for the different types of modelling. Seismic calculations are performed considering the actually recorded accelerograms of that earthquake, and the obtained results are compared with the really observed structural damages, in order to propose suitable strengthening techniques based on a better understanding of structural aspects most directly responsible for the damages. In this context, analysis and discussion are included concerning the influence of modelling type on the peak principal stresses and their zones of occurrence. By comparing those results with the actual damages, it is possible to assess the realism of the modelling hypotheses and then infer which one is most suitable. Based on those conclusions, some strategies are proposed to rehabilitate and strengthen the two churches structures.